2014
DOI: 10.1016/j.pharmthera.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The purinergic neurotransmitter revisited: A single substance or multiple players?

Abstract: The past half century has witnessed tremendous advances in our understanding of extracellular purinergic signaling pathways. Purinergic neurotransmission, in particular, has emerged as a key contributor in the efficient control mechanisms in the nervous system. The identity of the purine neurotransmitter, however, remains controversial. Identifying it is difficult because purines are present in all cell types, have a large variety of cell sources, and are released via numerous pathways. Moreover, studies on pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 542 publications
(905 reference statements)
2
59
0
Order By: Relevance
“…ATP (20), NAD + (14,15,21), and adenosine 5′-diphosphate ribose (ADPR) (17) activate P2Y1R and SK channels and might be inhibitory neurotransmitters in the colon (22). Because Up4A appears to stimulate P2Y1Rs in endothelium, and P2Y1Rs are important for purinergic signaling in the colon, we investigated whether Up4A is released in colonic muscle, whether Up4A affects membrane potentials and contractions of colonic muscles, whether Up4A is an agonist for P2Y1R, whether cells expressing PDGF receptor α (PDGFRα) are targets of Up4A, and how Up4A is metabolized in colons of humans and mice.…”
mentioning
confidence: 99%
“…ATP (20), NAD + (14,15,21), and adenosine 5′-diphosphate ribose (ADPR) (17) activate P2Y1R and SK channels and might be inhibitory neurotransmitters in the colon (22). Because Up4A appears to stimulate P2Y1Rs in endothelium, and P2Y1Rs are important for purinergic signaling in the colon, we investigated whether Up4A is released in colonic muscle, whether Up4A affects membrane potentials and contractions of colonic muscles, whether Up4A is an agonist for P2Y1R, whether cells expressing PDGF receptor α (PDGFRα) are targets of Up4A, and how Up4A is metabolized in colons of humans and mice.…”
mentioning
confidence: 99%
“…3b). Recent literature has shown that NAD + is stored in secretory granules and released from nerve endings in visceral smooth muscles and acts as an inhibitory neurotransmitter [41,42]. However, involvement of the SLC17A9 protein in the vesicular storage of NAD + is unlikely, because it does not recognize NAD + as a transport substrate [Sawada and Moriyama, unpublished observation].…”
Section: Identification Of Vesicular Nucleotide Transportermentioning
confidence: 99%
“…Astrocytes are known to release significant amounts of ATP in physiological and pathological conditions through different pathways (as reviewed in [37]). One possible ATP secretion pathway is represented by gap junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Among neurotransmitters, purines and mainly ATP, abundantly released by glial cells, have emerged as key contributors in the control of central functions [22][23][24]. ATP release might occur in several different ways: vesicular exocytosis [25][26][27][28], through anion channels [29][30][31][32], ATP-activated channel P2X7 [33], connexin hemichannels [34][35][36] (for review see [37]). Several conditions might determine ATP release: stimulation of ionotropic glutamate receptors in astrocytes [38]; intracellular Ca2+ increase [39]; mechanical stimulation [40]; bradykinin stimulation [41].…”
Section: Introductionmentioning
confidence: 99%